2014
DOI: 10.15448/1980-6108.2014.1.15319
|View full text |Cite
|
Sign up to set email alerts
|

Variação na prevalência de risco nutricional em indivíduos hospitalizados conforme cinco protocolos de triagem nutricional

Abstract: Objetivos: Verificar a prevalência de risco nutricional em indivíduos hospitalizados e a concordância no diagnóstico nutricional através de cinco protocolos de triagem nutricional. Métodos: Um estudo transversal incluiu pacientes de ambos os gêneros, maiores de 18 anos, admitidos no hospital no período de janeiro a março de 2013. Dentro das primeiras 48 horas de internação, foram aplicados os seguintes protocolos de triagem nutricional: Mini Nutrition Assessment (MNA); Mini Nutrition Assessment Short Form (MNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…SGA classifies the patients as well- nourished, moderately malnourished, and severely malnourished; on the other hand, the Nutritional Risk Screening classifies the priority of nutritional intervention. 8 For this study, we chose to work with SGA, since it is considered the gold-standard procedure in nutritional assessment of inpatients. 9 However, adequate training of all observers who desire to use it is crucial, because its precision depends on the capacity of the observer to detect significant nutritional alterations by means of subjective evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SGA classifies the patients as well- nourished, moderately malnourished, and severely malnourished; on the other hand, the Nutritional Risk Screening classifies the priority of nutritional intervention. 8 For this study, we chose to work with SGA, since it is considered the gold-standard procedure in nutritional assessment of inpatients. 9 However, adequate training of all observers who desire to use it is crucial, because its precision depends on the capacity of the observer to detect significant nutritional alterations by means of subjective evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…ASG classifica os pacientes como bem-nutridos, moderadamente desnutridos e gravemente desnutridos; já a Nutritional Risk Screening classifica a prioridade de intervenção nutricional . 8 Para este estudo, optou-se por trabalhar com a ASG, por ser um procedimento considerado padrão-ouro na avaliação nutricional de pacientes hospitalizados, 9 mas faz-se indispensável o treinamento adequado de todos os observadores que desejam praticá-la, pois sua precisão depende da capacidade do observador detectar as alterações nutricionais significativas por meio da avaliação subjetiva. 10 …”
Section: Introductionunclassified
“…The prevalence of nutritional risk in hospitalised patients identified by the original MUST varies among the studies reported in the literature . A cohort study conducted in Israel involving 215 elderly patients who underwent hip surgery identified nutritional risk in 20.4% of the sample .…”
Section: Discussionmentioning
confidence: 99%
“…Silva 19 Um estudo desenvolvido com 52 idosos hospitalizados, em Minas Gerais, obteve 38% de idosos com desnutrição. 20 A frequência elevada de idosos com desnutrição e risco de desnutrição é comum em várias populações, em especial os idosos internados ou institucionalizados, isso se deve as patologias, que muitas vezes levam à perda ponderal pela redução da ingestão de alimentos.…”
Section: Discussionunclassified